1997
DOI: 10.1021/bi961940s
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Muscarinic Receptors. Relationship between the G Protein and Multiple States of Affinity

Abstract: An expanded version of the mobile receptor model has been assessed in studies on the binding of N-[3H]methylscopolamine and [35S]GTPgammaS to cardiac muscarinic receptors and their attendant G proteins in ventricular membranes from hamster. The model comprises two pools of receptor, one of which lacks G proteins, and a heterogeneous population of G proteins that compete for the receptor within the G protein-containing pool. To guide the formulation of the model itself and to define the various parameters, data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…Whereas the nucleotide-sensitive binding of agonists to myocardial membranes is inconsistent with the notion of a transient 1 : 1 complex between receptor and G protein (Lee et al 1986;Green et al 1997), the data can be described in terms of cooperativity within a receptor that is at least tetravalent . Cooperativity within a comparatively large aggregate also can account for otherwise paradoxical effects identified in the binding of radiolabeled antagonists to muscarinic receptor extracted from porcine atria in cholate-NaCl (Park et al 2002).…”
Section: Oligomers Of the M 2 Muscarinic Receptor 543mentioning
confidence: 90%
See 1 more Smart Citation
“…Whereas the nucleotide-sensitive binding of agonists to myocardial membranes is inconsistent with the notion of a transient 1 : 1 complex between receptor and G protein (Lee et al 1986;Green et al 1997), the data can be described in terms of cooperativity within a receptor that is at least tetravalent . Cooperativity within a comparatively large aggregate also can account for otherwise paradoxical effects identified in the binding of radiolabeled antagonists to muscarinic receptor extracted from porcine atria in cholate-NaCl (Park et al 2002).…”
Section: Oligomers Of the M 2 Muscarinic Receptor 543mentioning
confidence: 90%
“…It has been suggested that the multiple states of affinity are induced by the G protein in an otherwise homogeneous population of mutually independent sites Gilman 1987;Birnbaumer et al 1990). This widely held view is problematic, however, and it is particularly difficult to sustain on quantitative grounds (Lee et al 1986;Sinkins and Wells 1993;Green et al 1997). An alternative view attributes the observed heterogeneity to nucleotide-sensitive cooperative effects between interacting sites (Chidiac and Wells 1992;Chidiac et al 1997).…”
mentioning
confidence: 99%
“…Two versions of the model were considered: a general case in which no restriction was placed on the affinity of the G protein for the receptor (Scheme 2) and the extreme case in which the values of K G and K G.N were set arbitrarily at 10 Ϫ15 M, approximating a stable RG complex (Scheme 3). Both schemes were applied with one class of G protein, as proposed originally (27), and with two classes (G 1 and G 2 ), the members of which compete for a single site on the receptor (33). The latter case of Scheme 2 is a specific example of ligandbiased signaling, in that the preference of the receptor for G 1 or G 2 will be determined by the relative affinity of the agonist for the free receptor on the one hand and each RG j complex on the other.…”
Section: Table 1 Parametric Values For the Binding Of Oxotremorine-m mentioning
confidence: 99%
“…Scheme 2 is a variant of the ternary complex model (27) in which two different G proteins (G j , j ϭ 1 or 2) compete for a single site on the receptor (R) to form the spontaneously dissociating complex RG 1 or RG 2 (32,33 interact randomly with all receptors ([R] t ) within the relevant volume. The radioligand (P) and unlabeled ligands (A) bind to the receptor with equilibrium dissociation constants K P and K A , respectively, and a guanylyl nucleotide (N), such as GMP-PNP, binds to each G protein with the equilibrium dissociation constant K Nj .…”
mentioning
confidence: 99%
See 1 more Smart Citation